Morphological variations of the mandibular condyle as assessed from panoramic radiographic images: a literature review - Masyrifah, Nurul; Yunus, Barunawaty (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This literature review aims to analyze the morphological variations of the mandibular condyle as observed in panoramic radiographic images. It investigates recent findings on the correlation between condylar morphology and clinical factors, highlights the clinical relevance of these variations in diagnosis and treatment planning, and underscores the importance of early identification of structural abnormalities in dental practice. Review: A comprehensive literature search was conducted using databases including PubMed, ScienceDirect, and Google Scholar. Keywords used were: mandibular condyle, morphological variation, panoramic radiograph, and TMJ. Inclusion criteria comprised peer-reviewed studies published in English from 2015 to 2023 focusing on human panoramic radiographic evaluations of condylar morphology. Exclusion criteria included studies using only CBCT without panoramic comparisons, case reports, and studies on animal subjects. The review synthesized retrospective, cross-sectional, and observational studies with sample sizes ranging from children to older adults to identify common condylar morphologies and their clinical implications. Conclusion: Panoramic radiographs can effectively identify morphological variations of the mandibular condyle, such as round, flat, angled, convex, and rare bifid shapes. These variations are associated with factors like age, gender, dentition status, and occlusion. Understanding these differences is crucial for early diagnosis and proper management of temporomandibular disorders. Keywords: Morphological variations, mandibular condyle, panoramic radiography, temporomandibular joint, TMJ disorders